International Student Mobility, Opportunity, and the Voluntariness of Migration: A New Conceptual Approach - Brunner, Lisa; Streitwieser, Bernhard; Bhandari, Rajika (International Higher Education, 2024)
As higher education, migration, and mobility intertwine in increasingly complex ways, we need a new way to analyze international student mobility (ISM). Unpacking ISM’s “messiness” brings to light two key interfacing continua: first, the discretion to move, and second, opportunity through movement. Recognizing this confluence not only better explains the reproduction, amplification, dissolvement, and restructuring of privilege in international education, but also highlights the need to visibilize students from displaced, refugee, and forced-migrant backgrounds.